Digital Eduliteracy Practices in English Learning for Students of Equivalency Education - Haris Danial; Mohamad Syahrun Ibrahim; Jefriyanto Saud (CV. Ulil Albab Corp, 2023)
This community service program is one of the programs carried out by the proposing team to assist the digital eduliteration practice of learning English at PKBM Nurain, Kab. Bone Bolango. The objectives of organizing this service program are 1) Increasing the learning motivation of equivalency education students in English subjects; 2) Activate students in learning English without burdening the age gradation factor in learning; 3) Improving students' English competence in class, and 4) Supporting the process of learning English in class.The implementation of collaborative service activities at PKBM Nurain, Dunggala Village, Bone Bolango Regency, emphasized the aim of increasing the learning motivation of equality education students at PKBM Nurain. Through this program the lecturers can apply knowledge, skills and technology to deal with deficiencies and problems faced by students at PKBM Nurain Dunggala Village. The results obtained in this service are that the process of learning English can be developed innovatively through the application of YouTube-based learning video media so that the ability to understand material or concepts can develop significantly.